Assessment of Wireless Technologies for deployment in Intelligent Transportation System based on Internet of Things - Ali, Jahan; Hasan, Munirul; M. Nomani, Kabir; Alginahi, Yasser M. (Thirtyone Ventures (opc) Pvt. Ltd, 2017)
Use of Internet of Things (IoT) with modern wireless network is a trend of the emerging technologies for different systems which can be deployed in various kinds of environment to monitor, communicate with or control the associated elements in the system. The activities e.g., monitoring and communication by IoT can play an important role to design an Intelligent Transportation System (ITS). In this paper, we assess the suitability of IoT enabled wireless technology to be used for ITS. We performed some comparative study to find the best wireless technology that provides reliability, low cost, less power consumption and less data latency for next generation ITS.This technology will reduce energy consumption of the deployed IoT devices as well as ensure safety, efficiency and convenient for transportation systems.